Identification of new urinary gamma‐hydroxybutyric acid markers applying untargeted metabolomics analysis following placebo‐controlled administration to humans. Issue 6 (16th January 2019) - Steuer, Andrea E.; Raeber, Justine; Steuer, Christian; Boxler, Martina I.; Dornbierer, Dario A.; Bosch, Oliver G.; Quednow, Boris B.; Seifritz, Erich; Kraemer, Thomas
Abstract: Gamma‐hydroxybutyrate (GHB) is a short‐chain fatty acid that occurs naturally in the mammalian brain and is prescribed as a medication against narcolepsy or used as a drug of abuse. Particularly, its use as a knock‐out drug in cases of drug‐facilitated crimes is of major importance in forensic toxicology. Because of its rapid metabolism and resulting narrow detection windows (<12 hours in urine), detection of GHB remains challenging. Thus, there is an urgent call for new markers to improve the reliable detection of GHB use. In the framework of a randomized, placebo‐controlled, crossover study in 20 healthy male volunteers, urine samples obtained 4.5 hours post‐administration were submitted to untargeted mass spectrometry [MS, quadrupole time of flight (QTOF)] analysis to identify possible new markers of GHB intake. MS data from four different analytical methods (reversed phase and hydrophilic interaction liquid chromatography; positive and negative electrospray ionization) were filtered for significantly changed features applying univariate and multivariate statistics. From the resulting 42 compounds of interest, 8 were finally identified including conjugates of GHB with carnitine, glutamate, and glycine as well as the endogenous compounds glycolate and succinylcarnitine. While GHB conjugates were only detectable in the GHB, but not in the placebo group, glycolate and succinylcarnitine were present in both groups albeit significantly increased through GHB intake. Untargeted metabolomics proved as a suitable tool for the non‐hypothesis driven identification of new GHB markers. However, more studies on actual concentrations, detection windows, and stability will be necessary to assess the suitability of these markers for routine application. Abstract : Detection of the knockout drug gamma‐hydroxybutyric (GHB) acid remains challenging and new markers are of tremendous importance to improve reliable detection. Liquid chromatography–high resolution mass spectrometry (LC–HRMS) based metabolomics has been applied to identify new markers for GHB intake following a placebo‐controlled, crossover study in 19 healthy men. New conjugates of GHB with carnitine and amino acids has been identified that could be promising, improved markers for GHB detection.